2022
DOI: 10.1177/09514848211068620
|View full text |Cite
|
Sign up to set email alerts
|

Reducing hospital admissions and transfers to long-term inpatient care: A systematic literature review

Abstract: Individuals in need of long-term care and their relatives prefer to receive and give care in their domestic environment for as long as possible. Residential long-term care is to be avoided for as long as possible. To achieve this goal, the care setting must be optimally oriented to the needs of the person in need of care. Moreover, relatives who provide care must be professionally supported. The Regional Care Competence Center (ReKo), launched on October 1, 2019, is a quasi-experimental study (two groups and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…No contexto internacional, sistemas de saúde com modelos integrados de cuidado 3 estão consolidados e evidências 4,5 têm demonstrado que a continuidade da assistência previne internações hospitalares, reduz a utilização dos serviços especializados e necessidade de exames, além de impactar positivamente na qualidade de vida dos idosos, em especial nos casos de Doenças Crônicas Não Transmissíveis (DCNT). Em levantamento de investigações nacionais sobre utilização de serviços públicos de saúde nesse grupo etário, verificou-se que a maioria das pesquisas explora os pontos de atenção da rede de forma isolada, ou seja, analisa um nível de atenção específico 1,6,7 .…”
Section: Introductionunclassified
“…No contexto internacional, sistemas de saúde com modelos integrados de cuidado 3 estão consolidados e evidências 4,5 têm demonstrado que a continuidade da assistência previne internações hospitalares, reduz a utilização dos serviços especializados e necessidade de exames, além de impactar positivamente na qualidade de vida dos idosos, em especial nos casos de Doenças Crônicas Não Transmissíveis (DCNT). Em levantamento de investigações nacionais sobre utilização de serviços públicos de saúde nesse grupo etário, verificou-se que a maioria das pesquisas explora os pontos de atenção da rede de forma isolada, ou seja, analisa um nível de atenção específico 1,6,7 .…”
Section: Introductionunclassified
“…In the international context, health systems with integrated care models 3 are consolidated and evidence 4,5 has shown that continuity of care prevents hospital admissions, reduces the use of specialized services and the need for tests, in addition to positively impacting the quality of life of the older people, especially in cases of Chronic Noncommunicable Diseases (CNCD). In a survey of national investigations on the use of public health services in this age group, it was found that most studies explore the points of care in the network in isolation, that is, they analyze a specific level of care 1,6,7 .…”
Section: Introductionmentioning
confidence: 99%